The endosymbiotic dinoflagellates (Symbiodinium sp.) of corals are parasites and mutualists - Lesser, M.; Stat, Michael; Gates, R. (2013)
The evolutionary success and continued survival of reef-building corals under increasing environmental change will, in part, be determined by the composition of their endosymbiotic dinoflagellate communities (Symbiodinium sp.). Recent research suggests that differences in the phylotype composition of Symbiodinium in the same host can lead to different outcomes for the host when exposed to similar environmental conditions. One explanation for these observations is that symbioses between corals and Symbiodinium represent a continuum of interaction states that encompass mutualisms and parasitisms consistent with current evolutionary theory developed for other symbiotic systems. Here, we discuss the evidence supporting the existence of a parasitic to mutualistic continuum in Symbiodinium interactions and propose that a consideration of the evolutionary ecology of these associations will advance our understanding of how environmental change will influence the ecological outcomes in these important symbioses. We advocate that a robust taxonomic structure for Symbiodinium sp. and empirical studies on sexual reproduction in Symbiodinium, the stability of interaction states among Symbiodinium symbioses spatially and temporally and how interaction states change as the environment changes will generate data for models that accurately forecast how climate change will influence the persistence of corals and the reefs they structure. © 2013 Springer-Verlag Berlin Heidelberg.